386. A Reexamination of Disseminated Coccidioidomycosis: The Natural History in the Pre-Antifungal Era. (26th November 2018) - Bays, Derek; Thompson, George R; Reef, Susan; Snyder, Linda; Freifeld, Alana; Wilson, Machelle; Galgiani, John
Abstract: Background: While it has been previously well described that central nervous system (CNS) coccidioidomycosis (CM) is nearly always fatal without treatment, the natural history of non-CNS disseminated coccidioidomycosis (DCM) infections is not well characterized. The historical VA-Armed forces CM patient group provides a unique cohort of patients not treated with standard antifungals to characterize the natural history of non-CNS DCM. Methods: We conducted a retrospective study of 595 VA-Armed forces CM patients diagnosed between 1955 and 1958 and followed to 1966. Cohorts were identified as non-disseminated disease (487 patients), non-CNS DCM (72 patients), and CNS DCM (36). A combination of statistical analyses were used to compare demographic information, laboratory data including serologies and complete blood count data, symptom severity, fate of primary infection, and mortality. Results: There were significant differences in the ethnicity between the cohorts with trends toward increased Black and Filipino patients in the disseminated cohorts ( P < 0.001). There was a trend showing increased frequency of leukocytosis regardless of eosinophilia in the disseminated cohorts ( P = 0.009). Patients with disseminated disease presented with more severe symptoms ( P = 0.006). Primary fate of infection demonstrated decreased rates of residual pulmonary nodule in DCMs: 38.19% in non-DCM, 13.89% in non-CNS DCM, and 19.44% in CNS DCM ( P < 0.001). In addition, there were decreased rates of residual cavities in DCM: 33.26% in non-DCM, 8.33% in non-CNS DCM, and 8.33% in CNS DCM ( P < 0.001). Forty-five percent and 53% of patients in the non-CNS DCM and CNS DCM cohorts, respectively, developed dissemination with initial infection. Mortality at last known follow-up due to CM was significantly different across the cohorts: 1.03% in non-DCM, 15.28% in non-CNS DCM, and 77.78% in CNS DCM ( P < 0.001). Conclusion: This large retrospective cohort study helps further characterize the natural history of non-CNS DCM in comparison to CNS DCM in a population that was not treated with conventional antifungal therapy. While not as fatal as CNS DCM, non-CNS DCM shares many characteristics and has a high associated morbidity. Disclosures: All authors: No reported disclosures.